The Reality of Using Artificial Intelligence (AI) in Human Resources Management: An Applied Study on Teaching Members at King Saud University - Alqahatani, Ghada Ali Saad (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to identify the reality of the use of artificial intelligence in human resources management, its obstacles and requirements for its use from the point of view of the working faculty members. The researcher used the descriptive survey method and the questionnaire as a tool that was distributed to a sample of (54) faculty members. The results revealed that the use of artificial intelligence in human resources management at King Saud University obtained a total mean (2.82 out of 5), i.e. a moderate degree, and the obstacles to the use of artificial intelligence in human resources management at King Saud University obtained a total mean (3.67 out of 5). The requirements for the use of artificial intelligence in human resources management obtained a total mean (3.87 out of 5), that is, to a (high) degree. Based on the results of the study, the researcher recommended the necessity of providing the technical infrastructure and financial allocations for the use of artificial intelligence at the university with the provision of trainers specialized in artificial intelligence, the dissemination of the culture of artificial intelligence among individuals, and the conduct of further studies on this subject.
Keywords: Artificial Intelligence; Human Resources Management; King Saud University; Teaching Staff; Education